Early Onset Preeclampsia Is Associated With Glycocalyx Degradation and Reduced Microvascular Perfusion. Issue 4 (19th February 2019) - Weissgerber, Tracey L.; Garcia‐Valencia, Oscar; Milic, Natasa M.; Codsi, Elizabeth; Cubro, Hajrunisa; Nath, Meryl C.; White, Wendy M.; Nath, Karl A.; Garovic, Vesna D.
Abstract : Background: The endothelial glycocalyx is a vasoprotective barrier between the blood and endothelium. We hypothesized that glycocalyx degradation is present in preeclampsia, a pregnancy‐specific hypertensive disorder characterized by endothelial dysfunction and activation. Methods and Results: We examined the sublingual glycocalyx noninvasively using sidestream dark field imaging in the third trimester among women with normotensive pregnancies (n=73), early (n=14) or late (n=29) onset preeclampsia, or gestational diabetes mellitus (n=21). We calculated the width of the glycocalyx that was permeable to red blood cells (called the perfused boundary region, a measure of glycocalyx degradation) and the percentage of vessels that were filled with red blood cells ≥50% of the time (a measure of microvascular perfusion). In addition, we measured circulating levels of glycocalyx components, including heparan sulfate proteoglycans, hyaluronic acid, and SDC1 (syndecan 1), in a subset of participants by ELISA. Repeated‐measures ANOVA was performed to adjust for vessel diameter and caffeine intake. Women with early onset preeclampsia showed higher glycocalyx degradation, indicated by a larger perfused boundary region (mean: 2.14 [95% CI, 2.05–2.20]), than the remaining groups (mean: normotensive: 1.99 [95% CI, 1.95–2.02], P =0.002; late‐onset preeclampsia: 2.01 [95% CI, 1.96–2.07], P =0.024; gestational diabetes mellitus: 1.97 [95% CI, 1.91–2.04], P =0.004). The percentage of vessels that were filled with red blood cells was significantly lower in early onset preeclampsia. These structural glycocalyx changes were accompanied by elevated plasma concentrations of the glycocalyx components, heparan sulfate proteoglycans and hyaluronic acid, in early onset preeclampsia compared with normotensive pregnancy. Conclusions: Glycocalyx degradation and reduced microvascular perfusion are associated with endothelial dysfunction and activation and vascular injury in early onset preeclampsia.